PATHOLOGICAL CONDITION AND ABNORMALITY FOUND ON PANORAMIC RADIOGRAPHIC EXAMINATION BEFORE ORTHODONTIC TREATMENT - Barunawaty Yunus (Faculty of Dentistry, Universitas Indonesia, 2015)
Radiography is very useful as diagnostic aids and is widely used in dentistry. Panoramic radiography, as an inherent part of orthodontic examination, is a very useful in evaluating the condition of the jaw. This paper will discuss the role of panoramic radiography examination in pathologic condition and abnormalities of teeth and jaw to support the treatment planning of orthodontic treatment.